(untitled) (AYUSHDHARA, 2015)
In Ayurvedic Samhita Niruddha Prakash (phimosis) vyadhi (disease) is described to be formed because of vitiated Vata Dosha where constricted Shishnacharma (prepuce) covers Mani (glans penis). This creates obstructed, slow urine flow and the prepuce could not be retracted. Treatment described in Ayurvedic epics is dilatation of preputial meatus by Niruddhaprakash Nadiyantra and Vatadosh Shamak medicated tail (oil) Parishek (fomentation). Surgery is advised if this measure fails. Niruddha prakash has similar features to that of phimosis described in modern medical science. Recent researches shows that glans penis and prepuce has common epithelium and its complete separation essential for complete prepitual retraction exposing whole of glans may normally occur up to the age of 17 years. This may lead to wrong diagnosis of phimosis. Circumcision is considered as treatment of choice for phimosis. In this review article efforts have made to analyze description of Niruddha prakash in Ayurved Epics, and recent researches regarding development and separation of prepuce, non surgical treatment of phimosis for bypass of surgical and anaesthetic complications, and surgical procedure with less complications compared to circumcision that will preserve prepuce as it is important structure protecting glans and urethral meatus and also for coital pleasure.